Metabolic Syndrome Individuals With and Without Type 2 Diabetes Mellitus Present Generalized Vascular Dysfunction. Issue 4 (April 2015) - Walther, Guillaume; Obert, Philippe; Dutheil, Frédéric; Chapier, Robert; Lesourd, Bruno; Naughton, Geraldine; Courteix, Daniel; Vinet, Agnès
<x xml:space="preserve">Abstract</x> Objectives— The first objective of this study was to demonstrate differences within endothelial-dependent and endothelial-independent vasoreactivity in macro- and microcirculation beds among patients with metabolic syndrome (MetS) with and without type 2 diabetes mellitus (T2D) compared with healthy counterparts. The second objective was to determine relationships among the function of macro- and microvascular systems and abdominal adiposity, as well as inflammatory markers in the 3 groups. Approach and Results— Cross-sectional analyses of 53 patients with MetS without T2D and 25 with T2D, as well as aged 40 years and sex-matched healthy controls included microvascular (cutaneous blood flow measured with laser Doppler flowmetry in response to iontophoresis of acetylcholine and sodium nitroprusside), and macrovascular reactivity (flow-mediated dilation and nitrate-mediated dilation) along with anthropometric measures, plasma glucose, and insulin and inflammatory markers. Compared with controls, MetS participants showed depressed endothelial function of both micro- and macrocirculation beds. T2D in patients with MetS revealed an exacerbated vascular smooth muscle dysfunction in micro- and macrocirculation compared with MetS without T2D. Indices of micro- and macrocirculation were predominantly inversely related to abdominal fat and inflammatory markers. Conclusions— MetS was associated with endothelial-dependent and endothelial-independent dysfunction, affecting both the macro- and the microvascular systems. Participants with diabetes mellitus demonstrated the most severe smooth muscle dysfunction. The presence of central abdominal fat and systemic inflammation seems implicated in the pathogenesis of vascular dysfunctions in MetS.